2013
DOI: 10.1038/oncsis.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine kinase 6 regulates mammary gland tumorigenesis in mouse models

Abstract: Protein tyrosine kinase 6 (PTK6, also called BRK) is an intracellular tyrosine kinase expressed in the majority of human breast tumors and breast cancer cell lines, but its expression has not been reported in normal mammary gland. To study functions of PTK6 in vivo, we generated and characterized several transgenic mouse lines with expression of human PTK6 under control of the mouse mammary tumor virus (MMTV) long terminal repeat. Ectopic active PTK6 was detected in luminal epithelial cells of mature transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 55 publications
(90 reference statements)
2
18
0
Order By: Relevance
“…Recently, PTK6 was shown to be regulated by hypoxia-inducible factors 1α/2α and proposed to be a mediator of hypoxia-induced breast cancer progression [39]. Similar to findings in human breast cancer, we recently demonstrated that PTK6 is induced in mouse mammary gland tumors of different origins, including spontaneous tumors and ERBB2 (HER2) induced tumors [23]. …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Recently, PTK6 was shown to be regulated by hypoxia-inducible factors 1α/2α and proposed to be a mediator of hypoxia-induced breast cancer progression [39]. Similar to findings in human breast cancer, we recently demonstrated that PTK6 is induced in mouse mammary gland tumors of different origins, including spontaneous tumors and ERBB2 (HER2) induced tumors [23]. …”
Section: Discussionsupporting
confidence: 56%
“…Without enrichment for epithelial cells, the epithelium may not have been well represented in surgical discard tissues that would also have included adipose, endothelial and connective tissue. While we have not detected Ptk6 protein or transcripts in the normal mouse mammary gland [23, 35], there may be distinctions in expression between species, related to lifespan and exposure to stress. PTK6 can be induced by stress and DNA damage in the intestinal epithelium and nontransformed cells where it promotes apoptosis [36-38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Brk increases cell proliferation and promotes anchorage independent growth, 14 a measure of transforming potential. Brk also promotes tumorigenesis in the mouse mammary gland, 35 and decreases tumor latency. 21 Knock-down of Brk inhibits cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…PTK6 protein expression has prognostic significance in breast cancer (Born et al, 2005;Aubele et al, 2009), and active PTK6 protein was detected in human breast tumors but not normal human mammary gland (Peng et al, 2014). Overexpression of PTK6 promotes mammary gland cancer tumorigenesis in mouse models (Lofgren et al, 2011;Peng et al, 2013). PTK6 sustains EGFR signaling via transactivation as well as by inhibition of EGFR degradation (Kang et al, 2010;Li et al, 2012).…”
Section: Breast Cancermentioning
confidence: 99%